Overview of the temporal trend of deaths and hospital admissions due to malignant neoplasia of the breast in Brazil, Northeast and Sergipe in the period from 1996 to 2020 (Research, Society and Development, 2022)
We aimed to estimate the temporal trend of mortality and hospital admissions for malignant breast neoplasm in Brazil, Northeast and Sergipe in the period 1996 to 2020. This is an ecological time-series study using public databases. The data were collected from the Mortality Information System (SIM/DATASUS). The information was arranged using descriptive statistics: mean, standard deviation, minimum and maximum. The standardized mortality rate (PMR) was calculated by the direct method and used for trend estimation, carried out by means of linear regression with Prais-Winsten autocorrelation correction. High mortality and hospitalization rates were evidenced over the time series. In this scenario, the Annual Percentage Variation (APV) of mortality shows the highest growth in Sergipe (APV=3.81%), followed by the Northeast region (APV=2.95%) and Brazil (APV=0.37%). In terms of hospitalizations, the Northeast presented the highest growth (APV=4.35%), followed by Brazil (APV=2.34%) and Sergipe (APV=1.39%). The present study exhibited increasing trends in mortality and hospitalization for malignant breast neoplasm in Brazil, Northeast and Sergipe. Therefore, it is essential that public policies, especially the encouragement of early detection, are improved to reduce mortality from this easily diagnosed disease with the possibility of cure.